2018
DOI: 10.18632/aging.101623
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα pathway involved in hepatic triglyceride metabolism disorder in diet-induced obesity mice following Escherichia coli Infection

Abstract: To investigate the different effects of acute pulmonary infection induced by Escherichia coli (E. coli) on lipid metabolism between diet-induced obesity (DIO, fed with high-fat diet) mice and lean mice. A total of 180 ICR mice were selected to be challenged intranasally with phosphate-buffered saline or 109 CFUs/mL of E. coli, and the body character indexes, biochemical indexes and expressions of genes and proteins involved in lipid metabolism were examined pre- and post-infection. Results revealed that, befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…CPT1 includes three isozymes, with CPT1A being the most abundant in the liver. As shown in the summary of metabolic pathways in Figure 9 [ 11 , 15 , 16 , 17 ], we selected downstream CPT1A as the target protein and demonstrated that AG extract significantly enhanced CPT1A protein expression, which is consistent with previous findings [ 11 ]. In additional, Zeng et al [ 18 ] reported that AG extract and ampelopsin inhibited the protein expression of SREBP-1c, fatty acid synthase (FAS), and ACC, which were responsible for lipogenesis in the liver; however, in comparisons with CPT1A, the effects of AG extract on these proteins appeared to be weaker.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…CPT1 includes three isozymes, with CPT1A being the most abundant in the liver. As shown in the summary of metabolic pathways in Figure 9 [ 11 , 15 , 16 , 17 ], we selected downstream CPT1A as the target protein and demonstrated that AG extract significantly enhanced CPT1A protein expression, which is consistent with previous findings [ 11 ]. In additional, Zeng et al [ 18 ] reported that AG extract and ampelopsin inhibited the protein expression of SREBP-1c, fatty acid synthase (FAS), and ACC, which were responsible for lipogenesis in the liver; however, in comparisons with CPT1A, the effects of AG extract on these proteins appeared to be weaker.…”
Section: Discussionsupporting
confidence: 86%
“…Since abnormal lipid metabolism in the liver is always regarded as the main reason for obesity, many research groups have focused on lipid metabolism and its related mechanisms in the liver. Fang et al reported that AMPKα inhibited the expression of sterol regulatory element binding protein 1c (SREBP-1c) and up-regulated the transcription levels of peroxisome proliferation-activated receptor α (PPARα), thereby affecting lipogenesis and lipid oxidation in the liver [ 15 ]. Shimoda et al revealed that purple tea extract significantly suppressed increases in body weight and abdominal and liver fat accumulation associated with HFD-induced NAFLD in mice by up-regulating the expression of CPT1A in the liver [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Corrales-Medina and colleagues found that obesity may exert a protective effect against 30-day mortality from community-acquired bacterial pneumonia [20]. Our previous studies showed that compared with the lean mice, the diet-induced obese (DIO) mice exhibited lower neutrophil infiltration and contents of proinflammatory cytokines and oxidative stress, and less severe histopathological lesions in the lung, as well as slighter lipid metabolic disorders in the liver after intranasal instillations of non-fatal dose of E. coli [1416]. Moreover, a report has shown that community-acquired pneumonia could induce dysfunction of liver [17].…”
Section: Discussionmentioning
confidence: 99%
“…The diet-induced obese (DIO) mice, similarly, exhibited less severe lung injury and lower mortality than the lean mice after intranasal instillations of non-fatal dose of E. coli , which was associated with the delayed inflammatory response and oxidative stress by diet-induced obesity [14, 15]. Furthermore, the infection-induced lipid metabolic disorders were slighter in the DIO mice than in the lean mice through AMPKα pathway in the state of non-fatal pneumonia caused by instillation E. coli [16] .…”
Section: Introductionmentioning
confidence: 99%
“…1 According to statistics, the prevalence of hepatic steatosis is over 50% in patients with obesity, type 2 diabetes, and metabolic syndrome, with obesity and alcohol being its two major causes. 2,3 Fatty acids in the liver are mainly derived from food and adipose tissue, and the hepatocyte takes up free fatty acids to synthesize triacylglycerol (TG), cholesterol (TC), and phospholipids. TG is then released into the bloodstream along with lipoproteins.…”
Section: Introductionmentioning
confidence: 99%